Kajian plankton paska pembersihan tumpahan minyak di Tambling Wildlife Nature Conservation (TWNC), Provinsi Lampung - Herawati, Maria Edna; Effendi, Hefni; Mardiastuti, Ani (Jurnal Pengelolaan Lingkungan Berkelanjutan (Journal of Environmental Sustainability Management), 2024)
Changes in plankton community structure can be an indicator of environmental changes due to oil pollution.. Oil pollution occurs along the coast of the Tambling Wildlife Nature Conservation (TWNC) area. This research aims to determine the plankton structure community including: abundance, diversity index, evennes index and dominance index in the TWNC area. There are 4 classes of phytoplankton in aquatic areas, namely Cyanophyceae, Chlorophyceae, Bacillariophyceae, and Dinophyceae. There are 7 classes of zooplankton in waters, namely: Protozoa, Rotifera, Crustacea, Nematoda, Polychaeta, Gastropoda and Diptera. Phytoplankton ranged 708,694 – 14,295,651 cells/m3, diversity index 0.38 – 1.64 (medium), evennes index 0.14 – 0.75 (medium to high) and a dominance index 0.29 – 0.88. Zooplankton abundance ranged 6000 – 142,609 cells/m3, diversity index 0.9 – 1.77 (medium), evenness index 0.5 – 0.91 (medium to high) and dominance index 0.19 – 0.58. The presence of plankton in the TWNC area is not influenced by oil waste contamination because at the time of the research no exposure to oil waste was found..